Efficacy of CT Scan for Assessment of Headache (Medical Forum Monthly, 2024)
Objective: To determine the efficacy of CT scan for assessment of Headache.Study Design: Prospective / cross sectional studyPlace and Duration of Study: This study was conducted at the Radiology Department of RMDC Lahore from January 2018 to June 2018.Materials and Methods: This study included 136 patients with headache. All the patients had CT scan to find out the frequency of pathologies. Data was collected on a specially designed Performa and analyzed by using SPSS.Results: The mean age of the patients was 44.80 + 23.25 years [range 20 – 70]. There were 58 (42.6%) female patients and 78 (57.4%) male patient in the study. CT scan could identify the lesion among 11 (8%) patients, while in rest of 125 (92%) patients; CT scan did not identify any pathology. Sinusitis was the most common pathology detected among 4 (36.4%) patients followed by stroke seen among 3 (27.2%) patients.Conclusion: The diagnostic yield of CT scan in detecting lesion among patients with headache is low and radiation exposure is more.